Individual Variation in Response to Novel Food in Captive Capuchin Monkeys (Sapajus spp.) - Ventricelli, Marialba; Gratton, Paolo; Sabbatini, Gloria; Addessi, Elsa; Sgaraglia, Giulia; Rufo, Fabrizio; Sirianni, Giulia (Frontiers in Ecology and Evolution, 2022)
How animals respond to novelty may have important outcomes in terms of fitness. On the one hand, aversion to novel stimuli may reduce the risks of consuming potentially toxic food or encountering predators. On the other hand, the propensity to approach novel stimuli may allow individuals to explore novel food sources and more flexibly adapt to novel challenges. Different species and individuals may find different ways to balance the costs and benefits that novelty posits. To date, however, little is known on how response to novel food varies across individuals of the same species depending on their previous experience with novelty, risk attitude and presence of higher-ranking conspecifics. In this study, we assessed individual variation in response to novel food by testing captive capuchin monkeys (Sapajus spp.) in an unconstrained social context, where all individuals in a group were able to access the testing area on a voluntary basis. We provided familiar and novel food to 23 study subjects belonging to four social groups differing in (i) previous experience with novel food, (ii) risk attitude (as assessed by a previous risky decision-making task), and (iii) dominance rank. We predicted that, as individuals may generalize their previous experience to novel contexts, those with more previous experience with novel food would be less neophobic than those with less experience. Moreover, if neophobia is a facet of the individual’s risk attitude, we predicted that more risk-prone individuals would be less neophobic than less risk-prone ones. Finally, individuals might flexibly modify their food choices according to the presence of conspecifics; in this respect, we predicted that, in response to monopolization of preferred resources by higher-ranking individuals, lower-ranking individuals would prefer familiar over novel food in the absence of higher-ranking individuals, but would modify their preference in favor of novel food in the presence of higher-ranking individuals. None of these predictions were supported by our results. We observed, however, that neophobia, measured as the latency to retrieve a food item, was more pronounced in lower-ranking than higher-ranking individuals, and that males showed a generally stronger bias than females towards a quicker retrieval of familiar food.